Humanized reception of spontaneous demand in Primary Health Care (PHC) of a Family Health Unit (USF) - Monteiro, Carla Ozileila Oliveira; Mendes, Seyna Ueno Rabelo; D'Alessandro, Aline Almeida Barbaresco; Silva, Felismário Medeiros da; Modesto, Renan Pena; Almeida, Isabela Maria Moura; Pedreira, Layra Eugenio; Almeida, Hiago Costa de; Paiva, Maykon Jhuly Martins de; D'Alessandro, Walmirton Bezerra (Seven Editora, 2024)
Primary Health Care is the first level of the health system and the user’s gateway to services. It constitutes a physical and social environment that is closest to the community and requires professionals who work there to have a diverse and complex arsenal of technologies, including the humanization of care. It is noteworthy that welcoming users is essential to ensure the principles of the Unified Health System, enhancing a higher level of quality in care for users. The objective was to report the process of creating guidelines on reception within the UBS reception, with a view to improving the quality of services provided, identifying the potential and difficulties of the reception team’s work process. This is a qualitative study of the experience report type in the practice scenario of Centro de Saúde 1304 sul in the city of Palmas/TO. 11 people participated in the experience, including 05 receptionists, 04 community health agents and 02 nursing technicians. The plan for data analysis followed the Hollyday method for systematization. We held 2 workshops, fun activities, conversation circles to discuss each scene created and witnessed. The weaknesses highlighted by the participants were mapped, which served as elements to guide the development of welcoming guidelines at the health unit reception. The meetings allowed reflection on the receptionists’ practice and their relationship with users and other team members. This experience showed us that the reflection undertaken here will contribute to the search for answers to the main questions raised, as well as being able to be incorporated into the teams’ work process. DOI:https://doi.org/10.56238/sevened2024.001-022